Respiratory syncytial virus - Cane, Patricia (Perspectives in medical virology, 2007)
Respiratory syncytial virus (RSV) was first identified half a century ago in 1956. Following its discovery, the virus soon became recognised as a major viral pathogen causing extensive outbreaks of respiratory tract infections in both the very young and in vulnerable adults. It is an unusual virus in that it can cause repeated reinfections throughout life. The topics covered within this volume are wide ranging in scope from the most basic molecular biology of the virus to the clinical picture of RSV in the developing world. The internationally recognised experts were invited not only to review the present state of knowledge but also to give their perspective on the current situation and to identify the gaps and future requirements for research in an effort to stimulate new cross-cutting approaches to tackle this major viral pathogen.